Proposing a Seventh Philosophical Style: Interpersonalist: Response to Dru Johnson’s Biblical Philosophy - Meek, Esther Lightcap 1953-; Johnson, Dru 1974- (2024)
In Biblical Philosophy: A Hebraic Approach to the Old and New Testaments, Dru Johnson’s strategy just is the powerful and productive alignment between the philosophical style of Hebrew Scripture and all that premier scientific discoverer Michael Polanyi has said about the scientific enterprise. Polanyi provides the very lenses to notice significant, superior, philosophical dimensions in Scripture. In this essay, I suggest that we add a seventh philosophical style: interpersonalist. This addition highlights a couple of Johnson’s other key claims: Yahweh’s characteristic personal encounter with his people, and his desire for friendship—thus for their skilled discernment. It adds coherence and distinctive depth to the already existing six categories. And the interpersonalist conviction accredits later developments of personalist philosophy within an otherwise Hellenic Western philosophical tradition, including the stunning work of Polanyi himself.
Keywords: Rezension